2012
DOI: 10.1080/01930826.2012.751291
|View full text |Cite
|
Sign up to set email alerts
|

Developing E-Science and Research Services and Support at the University of Minnesota Health Sciences Libraries

Abstract: This paper describes the development and implementation of e-science and research support services in the Health Sciences Libraries (HSL) within the Academic Health Center (AHC) at the University of Minnesota (UMN). A review of the broader e-science initiatives within the UMN demonstrates the needs and opportunities that the University Libraries face while building knowledge, skills, and capacity to support e-research. These experiences are being used by the University Libraries administration and HSL to apply… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 8 publications
0
12
0
1
Order By: Relevance
“…Several articles concluded that, based on surveys and interviews with researchers, three new areas of information management and support were in demand by or at least of interest to researchers. These were the identification of grants and other funding [1], identification of potential research collaborators [1,2], and data management and retrieval [1][2][3][4]. These activities are not traditionally perceived as the domain of libraries.…”
Section: Stage 1: Literature Reviewmentioning
confidence: 99%
“…Several articles concluded that, based on surveys and interviews with researchers, three new areas of information management and support were in demand by or at least of interest to researchers. These were the identification of grants and other funding [1], identification of potential research collaborators [1,2], and data management and retrieval [1][2][3][4]. These activities are not traditionally perceived as the domain of libraries.…”
Section: Stage 1: Literature Reviewmentioning
confidence: 99%
“…One of these issues is inconsistencies between researchers, which translates to a lack of general lab-wide standards for workflow/ research protocol. Another issue identified by the results was a lack of digital space for data storage, which is a fairly common RDM issue across all disciplines (Anderson et al 2007;Buys and Shaw 2015;Henderson and Knott 2015;Johnson, Butler, and Johnston 2012;Westra 2010). While nearly all respondents reported that they used some kind of documentation method for their research data, only 38% of respondents reported using a metadata schema to describe their data; this is lower than what has been reported in other similar studies (Whitmire, Boock, and Sutton 2015;Tenopir et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…They already possess "expertise and training in skills like metadata, searching, and discovery, archiving and preservation, and knowledge management" (Federer, Lu and Joubert 2016, 52). These are areas that have been identified as core strengths of the library that can be applied to RDM support services (Cox and Pinfield 2014;Faniel and Connaway 2018;Johnson, Butler, and Johnston 2012;Yoon and Schultz 2017). Typically, providing training through educational workshops and consultations is an easy and effective way for an academic library to start RDM services, given that these are activities in which most libraries are already engaged (Akers and Doty 2013;Henderson and Knott 2015;Johnson, Butler, and Johnston 2012;Parsons 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Storage and the need for repositories came up in those surveys as well. 12 Parsons found that the top three areas of interest at the University of Nottingham were DMPs, storage, and cataloging/metadata. 13 …”
Section: Introductionmentioning
confidence: 99%